Utilization of ultrasound for the synthesis of calcium hydroxyapatite nanoparticles from cockle (Anadara Granosa) shells to improve surimi gel properties - Hasan, Mohamad Rais (2024)
Seafood loss can be reduced by reusing the waste from the industry. This study uses ultrasound to clean and transform cockle (Anadara granosa) shells into hydroxyapatite nanoparticles (HAp), as an ingredient to improve surimi gel properties. This can produce a sustainable surimi ingredient while minimizing waste generated by the industry. The effectiveness of ultrasonic cleaning was tested using continuous (0.18 W/cm2, 0.35 W/cm2, 0.41 W/cm2) and pulsed (0.35 W/cm2, 1:1 On-Off power ratio) modes for 15 and 25 min. The cleaning efficacy was assessed on the whiteness index (WI), morphology, and chemical composition of the shells, as well as the chemical composition and turbidity of the wash water. The clean shells were then used to extract the HAp, where ultrasonic treatment was done for 15 min. The HAp was evaluated on yield percentage, WI, morphology, chemical composition, crystallography, thermal, and surface properties. For the application, the ideal combination of components in the surimi formulation was assessed based on water-holding capacity (WHC), expressible moisture content (EMC), and cooking loss rate (CLR). Using this predetermined formulation, HAp at varying concentrations (0.1%, 0.5%, 1.0%, and 1.5%) was then added. The gels were assessed on WHC, EMC, CLR, rheology, texture profile analysis, microstructure, mineral composition, and thermal properties. The effective erosion for the cleaning was found at power intensity between 0.35 and 0.41 W/cm2 at 37 kHz for 15 min. In pulsed mode, efficacy increased with a 25-min treatment. Highintensity ultrasonic treatment did not impact yield percentage of HAp, WI, or particle shape, but did reduce particle size and distribution range. Crystallinity, crystallite size, and calcium content were also enhanced. It showed a higher specific surface area but lower thermal stability compared to commercial HAp. For the application, the ideal combination of surimi components was found at 3% NaCl, 89.9% paste, and 7.10% water. The addition of HAp to the surimi did not improve moisture retention. Instead, a more compact gel structure and enhanced textural qualities were seen with 0.1% HAp. Ultrasonic treatment during pretreatment and extraction improved the cleaning effectiveness and particle properties of HAp. The produced HAp can be a sustainable ingredient that improves the gel characteristics of surimi.